Phase 1 trial to model primary, secondary, and tertiary dengue using a monovalent vaccine - Camila D. Odio; Kelsey E. Lowman; Melissa Law; Rosemary A. Aogo; Sally Hunsberger; Brad J. Wood; Michael Kassin; Elliot Levy; Viviane Callier; Saba Firdous; Chloe M. Hasund; Charlie Voirin; et al. (BMC Infectious Diseases, 2023)
Abstract Background The four co-circulating and immunologically interactive dengue virus serotypes (DENV1-4) pose a unique challenge to vaccine design because sub-protective immunity can increase the risk of severe dengue disease. Existing dengue vaccines have lower efficacy in DENV seronegative individuals but higher efficacy in DENV exposed individuals. There is an urgent need to identify immunological measures that are strongly associated with protection against viral replication and disease following sequential exposure to distinct serotypes. Methods/Design This is a phase 1 trial wherein healthy adults with neutralizing antibodies to zero (seronegative), one non-DENV3 (heterotypic), or more than one (polytypic) DENV serotype will be vaccinated with the live attenuated DENV3 monovalent vaccine rDEN3Δ30/31-7164. We will examine how pre-vaccine host immunity influences the safety and immunogenicity of DENV3 vaccination in a non-endemic population. We hypothesize that the vaccine will be safe and well tolerated, and all groups will have a significant increase in the DENV1-4 neutralizing antibody geometric mean titer between days 0 and 28. Compared to the seronegative group, the polytypic group will have lower mean peak vaccine viremia, due to protection conferred by prior DENV exposure, while the heterotypic group will have higher mean peak viremia, due to mild enhancement. Secondary and exploratory endpoints include characterizing serological, innate, and adaptive cell responses; evaluating proviral or antiviral contributions of DENV-infected cells; and immunologically profiling the transcriptome, surface proteins, and B and T cell receptor sequences and affinities of single cells in both peripheral blood and draining lymph nodes sampled via serial image-guided fine needle aspiration. Discussion This trial will compare the immune responses after primary, secondary, and tertiary DENV exposure in naturally infected humans living in non-endemic areas. By evaluating dengue vaccines in a new population and modeling the induction of cross-serotypic immunity, this work may inform vaccine evaluation and broaden potential target populations. Trial Registration NCT05691530 registered on January 20, 2023.